Pendidikan islam di Era globalisasi - Mardinal Tarigan; Zinni Zelda Muniroh; Putri Nadila Lasei; Safirah Irda Zatayumni (Jurnal Dirosah Islamiyah, 2024)
Islamic education has a crucial role in building the character of the Indonesian nation amid the challenges of globalization. In this context, Islamic education is not just a transfer of knowledge, but also guides individuals to develop as a whole in accordance with Islamic teachings. The roles of Islamic and national education need to synergize, as reflected in the 2003 National Education System Law, to achieve inclusive and character-building-oriented education goals. Islamic values have great influence in shaping quality human character, especially since Islam is the majority religion in Indonesia. Therefore, the importance of discussing the contribution of Islam in building national identity and character becomes increasingly inevitable.